Tamed Agility Pragmatic Contracting and Collaboration in Agile Software Projects - Book, Matthias; Gruhn, Volker; Striemer, Rüdiger (Springer International Publishing : Imprint: Springer, 2016)
This book describes pragmatic instruments and methods that enable business experts and software engineers to develop a common understanding of complex software systems, to determine key requirements, and to manage projects in a way that fosters trust, encourages innovation and distributes risk fairly between clients and contractors. After an introduction to the fundamentals of agile software development in Part I, Part II describes the Interaction Room, an actual room where digitalization and mobilization strategies are developed, where technology potentials are evaluated, where software projects are planned and managed, and where business and technical stakeholders can communicate face to face, visualize complex relationships intuitively, and highlight value, effort and risk drivers that are keys to the project's success. After addressing these constructive aspects, the book focuses on the commercial aspects of software development: The adVANTAGE contract model described in Part III ensures that the insight-driven innovation process of software development does not just function, but is allowed to flourish in a trusted client-contractor relationship. Even though software contracting and construction may be grounded in two different academic disciplines, they are inseparable in practice, and how they interact is illustrated in the case study of developing a private health insurance benefit system in Part IV. Ultimately though, the success of every software project depends on the skills of the stakeholders. Part V therefore describes the qualification profile that software engineers and domain experts have to satisfy today. This book is aimed at CIOs, project managers and software engineers in industrial software development practice who want to learn how to effectively deal with the inevitable uncertainty of complex projects, who want to achieve higher levels of understanding and cooperation in their relationships with clients and contractors, and who want to run lower-risk software projects despite their inherent uncertainties.